Impact of community culture in use of medicines - Kamel, Fouad Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Out of 350 patient samples referred to Erbil hospitals among one year, a total of 209 positive infectious patients (121 infectious male and 88 infectious female) were collected. Samples were analyzed generally, by cultivated using the common culture media according to the type of samples (urinary tract infections , pneumonia, otitis media, pharyngitis , inflammation sinusitis, vaginites and septisemia ). The most frequently isolates bacteria in male and female's samples with variable rate were Stap. aurous isolates followed by strep. Klebsiella, Acinetobacter, Pseudomonas aeruginosa, Escherichia coli, Enter. Micro. Frequency of resistance to more of antibiotic seen. There was a difference in the resistance of isolated bacteria to antibiotics from patients despite the concerns of the development of the condition and its impact on the health of society due to misuse of antibiotics. The study summarized the presentation of the drug position and the recommendation to abide by the health conditions to protect society.